THE CORRELATION READING COMPREHENSION AND WRITING ABILITY OF STUDENTS OF SMA NEGERI 11 PALEMBANG - Jenny Elvinna Manurung (Universitas Tridinanti Palembang, 2020)
This study focused on finding out the correlation between reading comprehension and writing ability. This study was conducted using correlation research design. The population of this study investigated the tenth grade students of SMA Negeri 11 Palembang with the total number were 482 students. In selecting the sample of this study, cluster random sampling technique was implemented. There were 147 students participated as the sample. The writer collected data by using two instruments from reading and writing test. The result of this study showed that the level of students’ comprehension reading was in the average category. The analysis result showed the mean score of reading comprehension was 61.80. The level of students’ writing ability was in the average category. The analysis result showed the mean score of students’ writing ability was 6.2713. In analyzing the data of the correlation analysis it was found that there is a significant correlation between reading comprehension and writing ability. The results of this study showed that the correlation coefficient level between reading comprehension and writing ability was 0.323 with the significance value 0.000 that lower alpha value 0.05. Thus, reading comprehension gave positive contribution to students’ ability in writing.Keywords: reading comprehension, writing ability, and correlation